AMPEROMETRIC DETERMINATION OF MELAMINE WITH ASCORBIC ACID PROBE USING CARBON PASTE ELECTRODE MODIFIED BY NON-IMPRINTED POLYMER/MOLECULARLY-IMPRINTED POLYMER POLY-GLUTAMIC ACID - AYU SETYORINI (NIM : 20514026), DIAN
Melamine is an additive compound in plastic and kitchenware production. Nowadays, it had been found that melamine was added into milk to increase the number of nitrogen which is the primary element in milk protein. Melamine can form crystals in kidney and cause kidney damage. Thus, the production of milk must be controlled. This research aims to develope high sensitive and selective amperometry method to determine melamine in milk. In this study, indirect amperometry was conducted using ascorbic acid as a probe. CPE modified with two layer of polymer namely non-imprinted polymer (NIP) and molecularly imprinted (MIP) of poly-glutamic acid, which is selective and sensitive to ascorbic acid measurement, was used in this experiment. Melamine concentration was determined based on the decrease of ascorbic acid oxidation current due to melamine addition. The optimum potential for amperometric measurement was found to be 0.150 V vs Ag/AgCl and maximum sensitivity was found in 0.1 M PBS pH 6. Repeated measurement (n = 8) resulted in RSD of 2.72% showing good sensitivity of the method. The detection limit was 0.24 mM. Determination melamine in spike milk sample gave percent recovery of 96.1 %.